2000
DOI: 10.1109/72.822511
|View full text |Cite
|
Sign up to set email alerts
|

Output feedback control of nonlinear systems using RBF neural networks

Abstract: An adaptive output feedback control scheme for the output tracking of a class of continuous-time nonlinear plants is presented. An RBF neural network is used to adaptively compensate for the plant nonlinearities. The network weights are adapted using a Lyapunov-based design. The method uses parameter projection, control saturation, and a high-gain observer to achieve semi-global uniform ultimate boundedness. The effectiveness of the proposed method is demonstrated through simulations. The simulations also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
197
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(201 citation statements)
references
References 19 publications
0
197
0
4
Order By: Relevance
“…Neural network structure of RBF RBF, a kind of efficient feed-forward network, is based on function approximation theory [14]. As shown in Figure 1, RBF is formed of three layers, namely the input layer, hidden layer and output layer.…”
Section: Rbf Neural Networkmentioning
confidence: 99%
“…Neural network structure of RBF RBF, a kind of efficient feed-forward network, is based on function approximation theory [14]. As shown in Figure 1, RBF is formed of three layers, namely the input layer, hidden layer and output layer.…”
Section: Rbf Neural Networkmentioning
confidence: 99%
“…High gain and control saturation has also been considered in a similar way by (Jankovic, 1996;Seshagiri and Khalil, 2000) and they showed that the tracking error can be made as small as desired by increasing the observer and parameter adaptation gains.…”
Section: Control Design Using Rbf Neural Networkmentioning
confidence: 99%
“…[9][10][11][12][13] Adaptive output feedback control using a high-gain observer and radial basis function neural network was proposed for nonlinear systems represented by input-output models. [14,15] Also, a nonlinear adaptive flight control system was designed by backstepping and neural network controller. [16] In the previous works, stability analysis of the closed-loop system using the neural network is rather involved in mathematical development.…”
Section: Introductionmentioning
confidence: 99%